JARGON ANALYSIS AMONG CADET IN LATIHAN INTEGRASI TARUNA WREDA NUSANTARA XXXIII - ERDIANSYAH, FAUZUL ADHIM (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: language, community, cadet, military, jargon, word formation processes.   In language development, there are characteristics used by people in their communities, groups, or environment. A community has specific terms which isnot recognized by outsider. The terms are called jargon. One of communitiesusing jargon is military community. In this case, the writer analysed the jargonused by the cadets during Latihan Integrasi Taruna Wreda Nusantara XXXIIIalong with its word formation processes.  In this study, a qualitative approach is applied to analyze the jargon used by cadets in Latihan Integrasi Taruna Wreda XXXIII. The writer observes the data with theory proposed by Akmajian (2001) about jargon and theory of word of formation processes by Yule (2006). The instrument of this study is the writer's own interview guideline. The subjects of this study are last year cadets Latihan Integrasi Taruna Wreda Nusantara XXXIII.  Based on the result, the writer found 31 jargons used by cadets. The form of the jargons were five (5) coinage, three (3) borrowing, nine (9) compounding, four (4) blending, one (1) acronym, three (3), six (6) multiple processes. The most form of the word formation processes of jargon used by cadets in Latihan Integrasi Taruna Wreda Nusantara XXXIII is compounding. It can be concluded that the invention of jargon is affected by the background of the cadets’ activities both inside and outside the classroom. The writer suggests the students of English Literature to investigate communities in any locations to find differences jargon and its use. He suggests the students who are interested in Sociolinguistics study to apply other theories and methods. He also expects further researchers to associate with jargon, register, slang, and argot.